TINJAUAN YURIDIS TERHADAP PENGUASAAN TANAH NEGARA MELALUI SURAT PENGUASAAN TANAH DAN PELEPASAN HAK ATAS TANAH DI KECAMATAN SAMARINDA SEBERANG - Reni Tri Maharani (Journal of Law ( Jurnal Ilmu Hukum ), 2014)
ABSTRACT             In accordance with the mandate of the Constitution as stated in Article 33 Paragraph (3) of the Constitution of the Republic of Indonesia Year 1945, which reads: "Earth, Water and natural resources contained therein controlled by the State and in use for the greatest welfare of the people".             So based on Article 33 Paragraph (3) of the Constitution of the Republic of Indonesia Year 1945 then underlies the birth of regulatory legislation regarding land. Based on the results of this study concluded that the soil has a very vital for human life, human life can not be separated with the land because the land is a natural resource that has physical important role in fulfilling the needs of all human life.             Therefore, all matters relating to the land itself, then it should humans not only realize the significance of ownership, as well as from all forms of administration of the land it self.